The Impact of the Loss of a Child in the Prenatal Period on Marital and Family Life and the Religiosity of Women after Miscarriage - Aleksandra Kłos-Skrzypczak (Religions, 2023)
Experiencing the death of a child is one of the most difficult things a person can go through. The situation of parents who have lost a child during the prenatal period is burdened with a social taboo. In the public sphere, it is often referred as the “secret problem of women”. The aspect of religiosity is extremely important in experiencing mourning after a miscarriage. The study is of a theoretical–empirical nature. The purpose of this text is to emphasize the value of human life at every stage, including in the situation of miscarriage. Online questionnaire research was conducted on a sample of 77 women, supplemented by content analysis of three of the most popular virtual support groups for parents who have experienced child loss in Poland. The aim of the conducted research was to attempt to illustrate how women cope with the experience of miscarriage and how this experience affects marital and family relationships. The issue of faith and the depth of religious life were highlighted as elements that provide support to parents after miscarriage at various stages of mourning.